Cu(ii) and V(iv)O complexes with tri- or tetradentate ligands based on (2-hydroxybenzyl)-l-alanines reveal promising anticancer therapeutic potential. Issue 1 (8th December 2020) - Ribeiro, Nádia; Bulut, Ipek; Cevatemre, Buse; Teixeira, Carlos; Yildizhan, Yasemin; André, Vânia; Adão, Pedro; Pessoa, João Costa; Acilan, Ceyda; Correia, Isabel
Abstract : New Cu II - and V IV O amino acid complexes show antiproliferative activity mediated by apoptosis and genomic damage. Abstract : Four new ligand precursors (H2 L 1 –H2 L 4 ), derived from the Mannich condensation of two amino acids (l -Val and l -Phe) and two 3, 5-disubstituted phenols ( t -Bu or Me), and the corresponding oxidovanadium(iv ) (1–4 ) and copper(ii ) (6–7 ) complexes are synthesized. Two other related compounds (H2 L 5 and H2 L 6 ), containing an additional 2-methyl-pyridine arm, and the corresponding V IV O (5 ) and Cu II (8–9 ) complexes were also obtained. All metal complexes are monomeric in the solid state, having a solvent molecule or a chloride ion in the coordination sphere. The in vitro cytotoxic activity of all compounds is evaluated against cancer cells from different origins. The IC50 values at 72 h are in the range of 6–15 μM for HeLa cells, 4–17 μM for A-549 cells and >25 μM for MDA-MB-231 cells, except for [V IV OL 1 (CH3 OH)] (1 ) and [CuL 6 (H2 O)] (9 ). With the exception of H2 L 6, overall, the metal complexes are more cytotoxic than the corresponding ligand precursors. Globally, the cellular viability data show that (i) the l -Phe derived compounds are more cytotoxic than the corresponding l -Val complexes; (ii) the presence of the bulkier t -Bu groups increases the cytotoxicity; (iii) the presence of a 2-methyl-pyridine arm increases considerably the cytotoxicity; and (iv) the Cu II -complexes are more cytotoxic than the V IV O-compounds. Complexes [V IV OL 3 (CH3 OH)] (3 ), [CuL 3 (H2 O)] (7 ) and [CuL 5 (H2 O)] (8 ) were further evaluated and their mechanism of action was determined to be apoptosis, evidenced by AnnexinV staining and the increase in caspase 3/7 activity. Compounds 3, 7 and 8 also exhibit DNA cleavage activity, involving the formation of reactive oxygen species and were able to induce genomic damage in cells as determined by COMET assay.